Negative electrode material and preparation method and application thereof

By designing a structure including core, carbon clad layer and conductive material in the negative electrode material, and using the weaving structure of polymer salt and amorphous carbon layer, the existing negative electrode material lacks performance under high magnification and high temperature conditions is solved, efficient carrier transmission and electrolyte retention are achieved, and the overall performance of the battery is significantly improved.

CN119542380APending Publication Date: 2025-02-28ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411598754.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing negative electrode materials have insufficient kinetic performance, poor circulation performance, and excessive consumption of electrolyte under high-speed conditions, making it difficult to achieve comprehensive optimization of rate performance, cycle performance and high temperature resistance at the same time.

Method used

A negative electrode material structure is adopted including a core, a carbon cladding layer and a conductive material, wherein the carbon cladding layer consists of a first amorphous carbon layer and a polymer salt embedded therein, and the conductive material is located on the surface and/or inside of the carbon cladding layer.

Benefits of technology

It significantly improves the rate performance, cycle performance and high temperature resistance of the negative electrode material, realizes rapid carrier transmission and effective retention of electrolyte, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542380A_ABST
    Figure CN119542380A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material and a preparation method and application thereof. The negative electrode material includes: a core including a negative electrode active material; a carbon coating layer coating the core, the carbon coating layer including a first amorphous carbon layer and a polymer salt embedded in the first amorphous carbon layer; and the conductive material is positioned on the surface and / or inside the carbon coating layer. The negative electrode material realizes balanced improvement of fast charge performance, cycle performance and high temperature resistance, and can significantly improve the electrochemical performance of secondary batteries including lithium ion batteries and sodium ion batteries. The invention also provides a preparation method and application of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode material and a preparation method and application thereof. Background Art

[0002] With the continuous development of science and technology, the demand for secondary batteries (or batteries for short) in electronic products has grown rapidly, especially in the fields of electric vehicles and energy storage systems, which have put forward higher requirements for the fast charging capability, cycle life and high temperature stability of batteries. In this context, the manufacturing technology of batteries and the preparation technology of their key components (such as negative electrode materials) have become one of the important tasks of research and development. As an important component of the battery, the performance of the negative electrode material plays a vital role in the overall performance of the battery.

[0003] Since the first introduction of lithium-ion batteries in the 1990s, graphite has been used as the mainstream negative electrode material for lithium-ion batteries due to its advantages of low cost and stable performance. However, with the rapid development of the new energy industry, the market's requirements for battery capacity and rate performance have continued to increase. Traditional graphite materials have gradually exposed their inherent shortcomings under high-rate conditions, such as poor kinetic performance, limited cycle capacity, and rapid electrolyte consumption, which restrict the widespread use of graphite materials. In addition to graphite, soft carbon and hard carbon have also been gradually used in negative electrode materials for lithium-ion batteries and are widely used in sodium-ion batteries. However, soft carbon and hard carbon also have similar problems, such as insufficient kinetic performance and poor cycle performance under high-rate conditions. Therefore, improving the performance of secondary batteries by modifying these materials is still one of the key directions of current research. At present, some studies have attempted to modify negative electrode materials such as graphite through coating technology. Although the above technology can improve the performance of negative electrode materials in some aspects, it is difficult to balance and improve the overall performance of the battery. For example, it is difficult to achieve comprehensive optimization of rate performance, cycle performance, high temperature resistance, etc. at the same time.

[0004] Therefore, it is still necessary to develop a new negative electrode material to improve the battery's overall kinetic performance, cycle performance and high temperature resistance to meet the growing market demand. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a negative electrode material that achieves balanced improvement in fast charging performance, cycle performance and high temperature resistance, and can significantly improve the electrochemical performance of secondary batteries including lithium-ion batteries and sodium-ion batteries.

[0006] The invention also provides a method for preparing the negative electrode material.

[0007] The invention also provides a negative electrode sheet.

[0008] The invention also provides a lithium ion battery.

[0009] The invention also provides an electric device.

[0010] The first aspect of the present invention relates to a negative electrode material, comprising: a core, the core comprising a negative electrode active material; a carbon coating layer coating the core, the carbon coating layer comprising a first amorphous carbon layer and a polymer salt embedded in the first amorphous carbon layer; a conductive material, the conductive material being located on the surface and / or inside the carbon coating layer.

[0011] The negative electrode material of the first embodiment of the present invention has at least the following beneficial effects:

[0012] In the negative electrode material, the carbon coating layer includes a first amorphous carbon layer and a polymer salt embedded in the first amorphous carbon layer, wherein the polymer salt easily attracts solvent molecules carrying carriers (such as lithium ions or sodium ions), reduces the resistance of carriers to escape from the solvent molecules, effectively improves the desolvation resistance of the electrolyte on the surface of the pole piece, and realizes the rapid transmission of carriers. Compared with ordinary polymers (non-salt state), the use of polymer salts is more conducive to the exchange and transfer of carriers, thereby improving the rate performance, while the use of ordinary polymers cannot achieve this purpose. In addition, polymer salts do not participate in electrochemical reactions, do not consume carriers during the charge and discharge process of the battery cell, and improve the cycle performance. Compared with the solution of only coating amorphous carbon, the presence of polymer salts can reduce the degree of side reactions between the negative electrode active material and the electrolyte, improve high temperature resistance and cycle performance, mainly because the amorphous carbon layer has a porous structure and is easy to react with the electrolyte at high temperature. By adding polymer salts, the probability of side reactions is reduced.

[0013] In the first carbon coating layer, the first amorphous carbon layer effectively improves the conductivity of the polymer salt, and the first amorphous carbon layer is used to form a chimeric structure with the polymer salt, giving full play to the anchoring effect of the amorphous carbon layer on the polymer salt, improving the binding force between the polymer salt and the negative electrode active material, making the polymer salt more firmly coated on the surface of the negative electrode active material, and improving the cycle performance. The amorphous carbon layer has a protective effect on the polymer salt, preventing the polymer salt from dissolving into the solvent and destroying the original coating layer structure during the subsequent preparation of the pole piece homogenization process, thereby improving the performance stability of the subsequent process.

[0014] The conductive layer can improve the overall conductivity of the negative electrode material, reduce the charge transfer impedance during the ion deintercalation process, promote the electron exchange during the ion deintercalation process, increase the carrier transfer rate at the interface of the electrode, and improve the rate performance. When the surface of the first carbon coating layer is coated with a conductive material, this part of the conductive material can construct a surface with a three-dimensional porous structure, form an electrolyte storage space, increase the electrolyte retention capacity of the electrode, and further promote the efficient transmission of carriers.

[0015] By designing the surface coating of the negative electrode material, a higher rate performance is achieved, which enables fast charging and discharging, and at the same time, excellent cycle performance and high temperature resistance are obtained. The results show that the constant current charging capacity at a 3C charging rate reaches more than 87.1% of the total capacity; at a high temperature of 45°C, the capacity retention rate after 800 cycles of charging and discharging at a rate of 1C is as high as 88.6%; after being placed at a high temperature of 60°C for 30 days, at a discharge rate of 0.33C, the capacity retention rate is as high as 87.2%, which has good fast charging performance, high temperature resistance and long cycle performance.

[0016] According to some embodiments of the present invention, the first amorphous carbon layer in the carbon coating layer is selected from hard carbon or soft carbon.

[0017] According to some embodiments of the present invention, the carbon coating layer is obtained by sintering a blend of organic matter A and polymer salt to carbonize the organic matter A. The sintering adopts a selective carbonization process, which can form a more stable mosaic structure compared with the conventional blending coating method, and give full play to the anchoring effect of amorphous carbon on the polymer salt.

[0018] Specifically, the blend can be obtained by solution blending, which is conducive to uniform dispersion of organic matter A and polymer salt. To achieve selective carbonization, organic matter A with a carbonization temperature of T1 and polymer salt with a carbonization temperature of T2 can be selected (T1 < T2), and sintered at a temperature of T (T1 < T < T2) to obtain a carbon coating layer in which the polymer salt is embedded in the first amorphous carbon layer.

[0019] According to some embodiments of the present invention, the carbonization temperature of the organic matter A is T1, the carbonization temperature of the polymer salt is T2, the softening temperature of the polymer salt is T0, the sintering temperature is T, and T, T0, T1, and T2 satisfy the following relationship: T1<T<T2, and T0<T. Furthermore, at temperature T, the organic matter A is carbonized to produce holes, and the polymer salt can enter the holes after softening to form a more stable mosaic structure. Specifically, T can be made as close to T1 as possible, and T2 can be as high as possible above T1 to reduce the impact of the carbonization process on the polymer salt.

[0020] According to some embodiments of the present invention, the temperature difference between T and T1 is 50-180°C, and the temperature difference between T2 and T1 is 50-300°C.

[0021] According to some embodiments of the present invention, T>200°C, for example, specifically 200-500°C, which is reasonably determined according to the carbonization temperatures of the organic matter A and the polymer salt, and a suitable T value between the two is selected.

[0022] According to some embodiments of the present invention, T0≤200°C, for example, specifically 90-200°C, and according to the sintering temperature T, a suitable T0 value less than T is selected.

[0023] According to some embodiments of the present invention, the mass ratio of the first amorphous carbon layer to the polymer salt is 1 to 5:1, specifically 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1 or any value between any two points. On the one hand, appropriately increasing the content of the first amorphous carbon layer is beneficial to improving the rate performance. On the other hand, the presence of a certain amount of polymer salt can reduce the side reaction between the negative electrode material and the electrolyte, and improve the cycle performance and high temperature resistance. Therefore, by optimizing the ratio of the two, the overall electrical performance can be balanced and optimized.

[0024] According to some embodiments of the present invention, the mass ratio of the first amorphous carbon layer to the polymer salt is 1 to 3:1, and further is 1.5 to 2.5:1.

[0025] According to some embodiments of the present invention, the organic substance A is selected from one or more of ethylene tar, coal tar, coal asphalt, rubber plasticizer (such as paraffin oil, etc.), styrene-butadiene rubber, urea-formaldehyde resin, monosaccharide compound, polysaccharide compound, carboxymethyl cellulose or its salt, polyacrylate or polyacrylate. Since polymer salts are generally water-soluble, organic substance A can be selected from water-soluble organic substances, such as monosaccharide compounds, polysaccharide compounds, carboxymethyl cellulose salts, polyacrylates, etc., or water-insoluble organic substances, and in this case, conventional aqueous dispersions of the organic substances, such as emulsions, etc., can be selected, so that it is easy to mix by solution method.

[0026] According to some embodiments of the present invention, the polymer salt is selected from a polymer lithium salt or a polymer sodium salt. The structures and ionic radii of lithium ions and sodium ions are relatively similar. When applied to lithium ion batteries or sodium ion batteries, the lithium ions or sodium ions in the polymer salt can promote the exchange and transfer of lithium ions or sodium ions in the electrolyte in the polymer salt, further improving the fast charging performance.

[0027] According to some embodiments of the present invention, the polymer salt is selected from at least one of lithium polyacrylate, sodium polyacrylate, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium alginate, and lithium alginate. Non-limiting examples of the polymer salt, for example, when applied to lithium ion batteries, can be selected from one or more of lithium polyacrylate, lithium carboxymethyl cellulose, and lithium alginate; when applied to sodium ion batteries, can be selected from one or more of sodium carboxymethyl cellulose, sodium polyacrylate, and sodium alginate.

[0028] According to some embodiments of the present invention, the polymer salt contains 0 to 5% carboxyl groups. For example, when the polymer salt is a carboxylate, the residual carboxyl content can be adjusted by controlling the carboxyl conversion rate. When all the carboxyl groups in the polymer are salted, the carboxyl content in the polymer salt is 0. Non-limiting examples of the carboxyl content in the polymer salt include: 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or any value between any two points.

[0029] According to some embodiments of the present invention, the polymer salt contains 1-5% carboxyl groups. Controlling the carboxyl content to be not too high is more conducive to ensuring high temperature resistance.

[0030] According to some embodiments of the present invention, the polymer salt contains 1 to 3% of carboxyl groups.

[0031] According to some embodiments of the present invention, the molecular weight of the polymer salt is 100W to 400W.

[0032] According to some embodiments of the present invention, the mass percentage of the carbon coating layer relative to the negative electrode material is 0.5% to 3%, for example, it can be 0.5%, 1%, 2%, 3% or any value therebetween.

[0033] According to some embodiments of the present invention, the mass percentage of the carbon coating layer relative to the negative electrode material is 1% to 3%.

[0034] According to some embodiments of the present invention, the conductive material is coated on the surface of the first carbon coating layer.

[0035] According to some embodiments of the present invention, the conductive material is selected from at least one of graphene, carbon nanotubes, conductive carbon black, and carbon fiber. The present invention does not restrict the type or size parameters of graphene, carbon nanotubes, conductive carbon black, and carbon fiber, and any known type can be selected. The present invention does not particularly limit the sheet diameter of graphene, and can be selected based on experience. As an example, the sheet diameter of graphene can be selected as 0.5 to 10 μm, further exemplified as 1 to 10 μm, or 1 to 5 μm, or 1 to 3 μm, or 1 to 2 μm; the number of graphene layers can be selected as 1 to 50 layers, and further exemplified as 1 to 30 layers. Carbon nanotubes can be selected as common multi-walled carbon nanotubes or single-walled carbon nanotubes. Conductive carbon black can be selected as acetylene black, Super P, Ketjen black, etc.

[0036] According to some embodiments of the present invention, the conductive material contains hydroxyl groups. The introduction of hydroxyl groups can increase the binding force between the conductive material and the polymer salt, especially when the polymer salt contains carboxyl groups, the condensation reaction of hydroxyl groups and carboxyl groups is used to promote the conductive material to be dispersed as much as possible near the polymer salt to improve electronic conductivity. The hydroxyl functional group can be introduced by known oxidation, acid washing, alkali washing and other processes, and the hydroxyl content can be easily controlled and adjusted by parameters such as reaction solution concentration, reaction temperature, reaction time, etc., without restrictive provisions.

[0037] According to some embodiments of the present invention, the mass content of hydroxyl in the conductive material is 1% to 5%, specifically 1%, 2%, 3%, 4%, 5% or any value between any two points. Controlling the hydroxyl content not to be too high is more conducive to ensuring high temperature resistance.

[0038] According to some embodiments of the present invention, the mass content of hydroxyl groups in the conductive material is 1% to 3%.

[0039] According to some embodiments of the present invention, the mass content of hydroxyl groups in the conductive material is 1% to 2%.

[0040] According to some embodiments of the present invention, the mass percentage of the conductive material relative to the negative electrode material is 0.05% to 2%, for example, it can be 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2% or any value therebetween. Conductive materials can improve electronic conductivity, fast charging performance and long cycle performance. Controlling the content of conductive materials to be not too high can reduce side reactions between the electrolyte and the negative electrode, and improve high temperature performance and long cycle performance.

[0041] According to some embodiments of the present invention, the mass percentage of the conductive material relative to the negative electrode material is 0.1% to 1%.

[0042] According to some embodiments of the present invention, the negative electrode material also includes a carbide of a dispersant. A certain amount of dispersant is added to improve the dispersibility of the conductive material. After the conductive material is dispersed inside the carbon coating layer and / or coated on the surface of the carbon coating layer, the added dispersant can be carbonized to improve the conductivity. In this case, the carbide of the dispersant is also included in the negative electrode material. Depending on the distribution of the conductive material, the carbide of the dispersant can be coated on the surface of the carbon coating layer and / or located inside the carbon coating layer.

[0043] According to some embodiments of the present invention, the dispersant is selected from at least one of polyvinylidene fluoride or its derivatives, carboxymethyl cellulose or its derivatives (such as oxidized carboxymethyl cellulose, carboxymethyl cellulose ester, oxidized carboxymethyl cellulose ester, etc.), carboxymethyl cellulose or its derivative salts (such as corresponding sodium salts, lithium salts, etc.), polyvinyl pyrrolidone or its derivatives, polyacrylic acid or its derivatives (such as polyacrylates), polyacrylic acid salts, polystyrene-butadiene rubber, polyacrylamide, polyimide, polyamide-imide, and phenolic resin. Derivatives include any known types derived from corresponding polymers by chemical reactions, and are not limited to the specific types listed.

[0044] Specifically, the dispersant may be of a suitable type having a carbonization temperature equivalent to that of the organic matter A, and the two types may be the same or different.

[0045] According to some embodiments of the present invention, the mass ratio of the dispersant to the conductive material is 1:1 to 10, for example, specifically 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any value between any two points. Since the amount of the dispersant is usually lower than, or at least not higher than, the amount of the conductive material, the carbide content formed after the dispersant is carbonized is significantly lower than the amount of the dispersant added, and the specific value can be easily calculated based on the type of dispersant and its carbon content.

[0046] According to some embodiments of the present invention, the mass ratio of the dispersant to the conductive material is 1:3-10.

[0047] According to some embodiments of the present invention, the mass ratio of the dispersant to the conductive material is 1:5-10.

[0048] According to some embodiments of the present invention, the negative electrode active material is selected from at least one of graphite, hard carbon or soft carbon. Specifically, graphite can be one or more of artificial graphite, natural graphite, and mesophase carbon microspheres. Graphite is mainly used as a negative electrode active material for lithium-ion batteries, and hard carbon or soft carbon can be used in both lithium-ion batteries and sodium-ion batteries.

[0049] According to some embodiments of the present invention, the particle size Dv50 of the negative electrode active material is 5 to 20 μm, for example, 5 μm, 7 μm, 10 μm, 12 μm, 15 μm, 17 μm, 20 μm or any value between any two points.

[0050] According to some embodiments of the present invention, the particle size Dv50 of the negative electrode active material is 7 to 16 μm.

[0051] According to some embodiments of the present invention, the mass percentage of the negative electrode active material relative to the negative electrode material is ≥90%.

[0052] According to some embodiments of the present invention, the mass percentage of the negative electrode active material relative to the negative electrode material is ≥91%.

[0053] According to some embodiments of the present invention, the mass percentage of the negative electrode active material relative to the negative electrode material is ≥95%.

[0054] According to some embodiments of the present invention, the surface of the core is coated with a second amorphous carbon layer, and the second amorphous carbon layer is located between the core and the carbon coating layer. The second amorphous carbon layer can improve the binding force between the carbon coating layer and the negative electrode active material, especially can promote the close binding of the polymer salt in the carbon coating layer and the negative electrode material, improve the structural stability of the carbon coating layer, and improve the coating uniformity of the carbon coating layer. In addition, the second amorphous carbon layer can effectively improve the overall conductivity of the negative electrode material, improve the liquid retention capacity and the desolvation rate of lithium, sodium and other ions on the surface of the negative electrode active material, and increase the active sites to improve the ion embedding rate.

[0055] According to some embodiments of the present invention, the second amorphous carbon layer is selected from hard carbon or soft carbon. Specifically, the second amorphous carbon layer is formed by carbonizing an organic substance B, and the organic substance B can be selected from one or more of ethylene tar, coal tar, coal pitch, rubber plasticizer, styrene-butadiene rubber, urea-formaldehyde resin, monosaccharide compounds or polysaccharide compounds.

[0056] According to some embodiments of the present invention, the mass percentage of the second amorphous carbon layer relative to the negative electrode material is 0.5% to 3%. Specifically, it can be 0.5%, 1%, 2%, 3%, or any value between any two points. Controlling the content of the second amorphous carbon layer to be not too high is more conducive to ensuring high temperature resistance.

[0057] According to some embodiments of the present invention, the mass percentage of the second amorphous carbon layer relative to the negative electrode material is 1% to 3%.

[0058] Another aspect of the present invention provides a method for preparing the negative electrode material, comprising the following steps:

[0059] S1, preparing a mixed solution 1 containing an organic substance A and a polymer salt;

[0060] S2, dispersing the raw materials including the core into the mixed solution 1 to form a mixed solution 2;

[0061] S3, drying the mixed solution 2, and then sintering it under a protective atmosphere to carbonize the organic matter A therein to form a carbon coating layer covering the core;

[0062] S4, preparing a mixed solution 3 containing a conductive material, dispersing the product obtained in step S3 in the mixed solution 3, and obtaining the negative electrode material after drying;

[0063] Or include the following steps:

[0064] S1', preparing a mixed solution 4 containing the polymer salt, organic matter A, core and conductive material, drying the mixed solution 4, and then sintering it under a protective atmosphere to carbonize the organic matter A therein to obtain the negative electrode material.

[0065] In the above method, the dispersant is used to improve the dispersibility of the conductive material, and carbonizing the dispersant is beneficial to ensuring the conductivity.

[0066] Through a multi-step method (steps S1-S4), after forming a carbon coating layer covering the core, a conductive material is coated on the surface of the carbon coating layer, and a structure containing a conductive material inside the carbon coating layer is prepared through a one-step method (step S1'). The preparation process can be adjusted according to actual needs. Under the premise of meeting the performance, the one-step method can simplify the process flow and save preparation time and cost.

[0067] The above method uses a mixed solution coating of organic matter A and polymer salt, and a selective carbonization and sintering process (organic matter A is carbonized, while polymer salt is not carbonized) to generate an in-situ mosaic structure of an amorphous carbon layer and polymer salt, which not only improves the conductivity of the negative electrode material, but also strengthens the binding force between the negative electrode surface and the polymer salt. This process route effectively ensures the efficient ion transmission capability of the material, improves the electrochemical reaction rate and the overall performance of the battery, especially under high rate and high temperature conditions, and ensures stability and life under long cycle conditions.

[0068] It should be noted that in step S3, by adjusting the ratio of organic matter A and polymer salt, for example, the ratio of the two satisfies: the mass ratio of amorphous carbon layer formed by carbonization of organic matter A: polymer salt is 1 to 5:1, a powdered product can be obtained directly after carbonization, or a powder material can be obtained by simple grinding without the need for a long crushing process such as ball milling.

[0069] It should be understood that in order to achieve selective carbonization, the sintering temperature should be appropriately higher than the carbonization temperature of the organic matter A and appropriately lower than the carbonization temperature of the polymer salt, for example, refer to the above-mentioned relevant implementation methods for negative electrode materials.

[0070] According to some embodiments of the present invention, the solid-liquid mass ratio of the mixed solutions 2-4 is independently selected from 1:1 to 5, wherein the solid-liquid mass ratio is the mass ratio of the solid phase to the liquid phase in the corresponding mixed solution.

[0071] According to some embodiments of the present invention, a dispersant is further added to the mixed solution 3, and step S4 further includes: carbonizing the dispersant after drying to obtain the negative electrode material; or, a dispersant is further added to the mixed solution 4, and in step S1', the organic matter A and the dispersant are carbonized by sintering to obtain the negative electrode material. The type and amount of the dispersant are selected with reference to the above-mentioned embodiments of the negative electrode material.

[0072] It should be understood that, in the case of adding a dispersant, the carbonization temperature of the dispersant should be lower than that of the polymer salt, and the sintering temperature in the above method is appropriately higher than the carbonization temperature of the dispersant, so that when the dispersant is carbonized, the polymer salt will not be carbonized. Specifically, the carbonization temperature of the dispersant can be determined by referring to the carbonization temperature T1 of the organic matter A mentioned above, and combined with the types of dispersants listed above, it is easy to select a suitable type of dispersant that meets the requirements.

[0073] According to some embodiments of the present invention, the negative electrode material also includes a second amorphous carbon layer, and the method for preparing the negative electrode material also includes: before step S1, coating the surface of the core with the second amorphous carbon layer, and further, it can be understood that the core of step S2 or step S1' is a core coated with the second amorphous carbon layer. Specifically, the method for forming the second amorphous carbon layer can adopt a well-known solid phase method, liquid phase method or gas phase method. Among them, the solid phase method, for example, is to coat the surface of the negative electrode active material with an organic substance B such as asphalt and place it in a carbonization furnace for carbonization; the liquid phase method, for example, is to slurry the negative electrode active material and the organic substance B, dry them, and carbonize them; the gas phase method, for example, is to use an organic carbon source (such as methane, ethylene, acetylene) for carbon deposition, and the deposition equipment can be a rotary kiln.

[0074] According to some embodiments of the present invention, the dispersed phase of the mixed solution 1, the mixed solution 3, and the mixed solution 4 is selected from one or more of water, NMP, ethanol, and ethylene glycol.

[0075] According to some embodiments of the present invention, the protective atmosphere is an inert atmosphere, specifically nitrogen, argon, etc.

[0076] Another embodiment of the present invention provides a negative electrode sheet, wherein the raw materials for preparing the negative electrode sheet include the negative electrode material.

[0077] The negative electrode sheet is based on the coating structure design of the negative electrode material, especially the intercalation structure design of the first amorphous carbon layer and the polymer salt, and the introduction of the conductive material, which effectively improves the overall conductivity and carrier transfer rate of the negative electrode sheet. The introduction of the polymer salt reduces the desolvation resistance of the negative electrode sheet during the charge and discharge process, realizes the rapid transfer of carriers, and significantly improves the rate performance. In addition, the presence of the polymer salt reduces the side reaction between the negative electrode material and the electrolyte, prolongs the service life of the negative electrode sheet, and makes it have excellent cycle stability and high temperature resistance.

[0078] It should be understood that the negative electrode sheet generally also includes a negative electrode current collector, a negative electrode conductor and a negative electrode binder. The specific selection of these components or the preparation technology of the negative electrode sheet is a conventional technology and can be easily selected according to actual needs.

[0079] Another aspect of the present invention provides a secondary battery including the negative electrode sheet described above.

[0080] This negative electrode material can significantly improve the charge and discharge rate performance in secondary batteries, especially in fast charging scenarios. The presence of polymer salts reduces the consumption of electrolytes, allowing the battery to maintain a high capacity retention rate after a long cycle, extending the overall service life of the battery. Through the combined action of the first amorphous carbon layer and the conductive material, the charge transfer impedance during ion insertion and extraction is reduced, and the stability of the battery and its tolerance in high temperature environments are improved. Therefore, based on the design of the negative electrode material, the secondary battery has good long cycle performance, fast charging performance and high temperature stability, which can better meet the requirements of high-performance application scenarios.

[0081] It should be understood that secondary batteries generally also include a positive electrode, a separator, and an electrolyte, and the related technologies are conventional technologies and can be easily selected according to actual needs.

[0082] According to some embodiments of the present invention, the secondary battery is a lithium ion battery or a sodium ion battery.

[0083] Another aspect of the present invention provides an electric device including the secondary battery described above.

[0084] The negative electrode material design ensures the battery's efficient and fast charging capabilities, meets the demand for high-rate fast charging, and extends the service life of electrical devices by reducing side reactions, improving cycle performance and high temperature resistance.

[0085] Electrical devices specifically include electric vehicles (such as electric cars, electric motorcycles, electric bicycles), energy storage systems (such as household energy storage systems, photovoltaic energy storage systems) or mobile devices (such as smart phones, tablets, laptops, etc.).

[0086] Herein, the term "plurality" means two or more than two.

[0087] "Approximately" means the error range is ±2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] Figure 1 It is a schematic diagram of the structure of the negative electrode material of the present invention.

[0089] Reference numerals:

[0090] 010, core; 020, second amorphous carbon layer; 030, carbon coating layer; 031, first amorphous carbon layer; 032, polymer salt; 040: conductive material. DETAILED DESCRIPTION

[0091] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0092] In the examples and comparative examples, the molecular weights of lithium polyacrylate and lithium carboxymethyl cellulose are 100W to 400W, and the softening points are 90 to 200°C.

[0093] The hydroxyl groups of graphene can be introduced by conventional acid modification methods, and the hydroxyl content can be easily adjusted by acid concentration, acid modification temperature and acid modification time.

[0094] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0095] Example 1

[0096] refer to Figure 1 A negative electrode material includes a core 010 and a second amorphous carbon layer 020, a carbon coating layer 030 and a conductive material 040 sequentially coated on the surface of the core 010. The carbon coating layer 030 includes a first amorphous carbon layer 031 and a polymer salt 032 embedded in the first amorphous carbon layer 031.

[0097] Among them, core 010 is artificial graphite, particle size D V The conductive material 040 is graphene, the sheet diameter is 1 to 2 μm, and the number of layers is 1 to 20.

[0098] The preparation method of the negative electrode composite material is as follows:

[0099] S1, preparing a mixed solution 1 containing an organic substance A and a polymer salt;

[0100] S2, dispersing the nuclei in the mixed solution 1 to form a mixed solution 2;

[0101] S3, drying the mixed solution 2, and then sintering it under a protective atmosphere to carbonize the organic matter A therein to form a carbon coating layer covering the core;

[0102] S4, preparing a mixed solution 3 containing a conductive material and a dispersant, dispersing the product obtained in step S3 in the mixed solution 3, and after drying, carbonizing the dispersant to obtain a negative electrode material.

[0103] The types and amounts of organic matter A, conductive material and dispersant are shown in Table 1 and Table 2.

[0104] The sintering temperature in step S3 and the carbonization temperature in step S4 are both 230° C., and the protective atmosphere is nitrogen. In step S3, since the proportion of organic matter A is higher than that of polymer salt, a powder product can be obtained after sintering without crushing.

[0105] The dispersed phases of the mixed solution 1 and the mixed solution 3 are both water, wherein the amount of water added to the mixed solution 1 is 2000 g, and the mass ratio of the solid phase to the liquid phase in the mixed solution 3 is 1:1-5.

[0106] In this embodiment, the preparation method of the negative electrode material is a multi-step method. Referring to the above, a one-step method can also be used to prepare a composite material. The distribution of the conductive material and the carbide of the dispersant is different. It should be understood that for the one-step method, the polymer salt 032 is embedded in the first amorphous carbon layer 031, including the polymer salt 032 embedded in the first amorphous carbon layer 031, and also embedded in the surface of the first amorphous carbon layer 031. The two states can coexist.

[0107] In step S1, both organic matter A and polymer salt are water-soluble, and mixed solution 1 is a mixed aqueous solution of the two, which can achieve uniform dispersion. Referring to the above, organic matter A can be a water-insoluble organic matter. In this case, a conventional dispersion (such as an emulsion) of the corresponding substance can be selected, and then, mixed solution 1 is an aqueous dispersion formed by dispersing organic matter A in a polymer salt solution.

[0108] After solution blending, the organic matter A and the polymer salt can be evenly dispersed, so that after sintering, a chimeric structure of the carbide of the organic matter A (i.e., the first amorphous carbon layer) and the polymer salt, i.e., the carbon coating layer 030, can be obtained. It can be understood that Figure 1 The carbon coating layer structure shown is only schematic, mainly used to show the mosaic morphology, and does not refer to the actual microscopic morphology of the carbon coating layer 030.

[0109] Examples 2 to 9, and Comparative Examples 1 to 5

[0110] The differences from Example 1 are shown in Table 1 and Table 2.

[0111] Specifically, in Example 8, the preparation method of the negative electrode composite material is:

[0112] S0, using the solid phase method, the raw material is asphalt, the asphalt carbon content is 60%, 1000g of the core (artificial graphite) and 33.33g of asphalt are mixed evenly and put into the carbonization furnace, and a nitrogen protective atmosphere is introduced, the sintering temperature is 1200°C, and the sintering is carried out for 12h to obtain a core coated with a second amorphous carbon layer;

[0113] S1, preparing a mixed solution 1 containing an organic substance A and a polymer salt;

[0114] S2, dispersing the cores coated with the second amorphous carbon layer in the mixed solution 1 to form a mixed solution 2;

[0115] S3, drying the mixed solution 2, and then sintering it under a protective atmosphere to carbonize the organic matter A to form a carbon coating layer covering the core;

[0116] S4, preparing a mixed solution 3 containing a conductive material and a dispersant, dispersing the product obtained in step S3 in the mixed solution 3, and after drying, carbonizing the dispersant to obtain a negative electrode material.

[0117] In Example 8, the remaining details of the preparation method are the same as in Example 1.

[0118] Comparative Example 6

[0119] A negative electrode material is prepared, wherein a polymer salt is coated on the surface of a first carbonized layer. The specific steps are:

[0120] S1, dispersing artificial graphite and organic matter A in water, drying, and carbonizing at temperature T to obtain powder 1;

[0121] S2, dispersing powder 1 and polymer salt in water, and drying to obtain powder 2;

[0122] S3, the powder 2, the conductive material and the dispersant are dispersed uniformly in water, dried, and sintered at a temperature T to obtain a negative electrode material.

[0123] Among them, the relevant material types, proportions and process parameters are shown in Tables 1 and 2.

[0124] Table 1

[0125]

[0126] Table 2

[0127]

[0128]

[0129] Test Case

[0130] Used to reflect the performance of negative electrode materials in lithium-ion batteries.

[0131] 1. Preparation of Lithium-ion Half-cell

[0132] In a dry argon environment, propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) (weight ratio of about 1:1:1) are mixed, and LiPF6 is added to the mixed solvent, mixed evenly, and an electrolyte is obtained, wherein the concentration of LiPF6 is about 1.15 mol / L. The negative electrode material, conductive carbon black, and binder CMC and SBR obtained in the embodiment and the comparative example are added to deionized water according to a weight ratio of about 94.5:1.5:1.5:1.5, stirred to form a slurry, and a coating with a thickness of about 100 μm is formed by a scraper coating, and dried in a vacuum drying oven at about 85°C for about 12 hours, and cut into discs with a diameter of about 1 cm by a punch in a dry environment, and a metal lithium sheet is used as a counter electrode in a glove box, and a Ceglard composite membrane is selected as the isolation membrane, and the above-mentioned electrolyte is added to assemble a button battery.

[0133] 2. Preparation of Lithium-ion Full Battery

[0134] 2.1. Preparation of negative electrode sheet

[0135] The negative electrode material, negative electrode conductive agent (conductive carbon black), binder SBR and thickener CMC obtained in the embodiment and comparative example are mixed in a weight ratio of about 96:1:1.6:1.4, and an appropriate amount of water is added, and kneaded at a solid content of about 60wt% to 75wt%. Add an appropriate amount of water to adjust the viscosity of the slurry to about 3000-8000Pa·S to prepare a negative electrode slurry. The prepared negative electrode slurry is coated on the negative electrode current collector copper foil with a wet film thickness of about 100μm, dried, and cold pressed to obtain a negative electrode sheet. Among them, the type and ratio of the negative electrode conductive agent, binder and thickener, as well as the proportion of the negative electrode active material, can be added according to actual conditions, and the preparation technology of the negative electrode sheet refers to the conventional method, and no restrictive provisions are made.

[0136] 2.2 Preparation of full battery

[0137] The prepared negative electrode sheet, positive electrode sheet, electrolyte and separator are assembled into a lithium-ion full battery according to conventional methods.

[0138] Among them, the positive electrode sheet is a positive electrode sheet for conventional lithium-ion batteries, and the positive electrode active material is LiFePO4; the diaphragm is a polyethylene porous polymer film. In addition, polypropylene diaphragms or composite diaphragms can also be selected.

[0139] The negative electrode sheet, separator, and positive electrode sheet are stacked in order, wound into a bare battery cell, placed in a battery shell, and injected with electrolyte (the same electrolyte used in the aforementioned half-cell). After packaging, standing, and formation processes, a lithium-ion battery is obtained.

[0140] 3. Test items

[0141] 3.1 Negative electrode test

[0142] Take the negative electrode sheet prepared in Section 2.1, cut it into a width of 20 mm and a length of L1, take the above electrolyte and put it in a beaker, then put the cut negative electrode sheet into the electrolyte, and partially immerse the negative electrode sheet in the electrolyte, and the immersion length is L2 (L2<L1). Record the time for the electrolyte to diffuse to the top of the electrode sheet as t, and the electrode sheet liquid absorption rate is (L1-L2) / t.

[0143] 3.2 Capacity Test

[0144] The prepared half-cell was charged and discharged using a LAND series battery testing system at a charge and discharge rate of 0.05C and a voltage of 5mV to 2V. The discharge capacity was recorded and the gram capacity of the negative electrode material was calculated.

[0145] 3.3 Charging rate test

[0146] At 25°C, discharge at 0.33C to 2.0V, let stand for 5 minutes, charge at 3C to 3.75V, charge at constant voltage to 0.05C and let stand for 5 minutes, the ratio of constant current charging capacity to total capacity (the sum of the capacities of constant current and constant voltage charging stages) is the charging rate.

[0147] 3.4 High temperature (45°C) cycle performance test

[0148] The test temperature is 45°C, and the battery is charged to 3.75V at 1C constant current, charged to 0.05C at constant voltage, and discharged to 2.0V at 1C after standing for 5 minutes. The discharge capacity obtained in this step is taken as the initial capacity, and a 1C charge / 1C discharge cycle test is performed. The ratio of the discharge capacity to the initial capacity of each cycle is recorded to obtain the capacity decay curve. The capacity retention rate after 800 cycles at 45°C is recorded to evaluate the high temperature cycle performance of the battery.

[0149] 3.5 High temperature (60°C) storage performance test:

[0150] At 25°C, charge to 3.75V at 0.33C constant current, charge to 0.05C at constant voltage, and discharge to 2.0V at 0.33C after standing for 5 minutes. The discharge capacity obtained in this step is the reference capacity C1. Place the battery cell in a high temperature box at 60°C for 30D and take it out. At 25°C, charge to 3.75V at 0.33C constant current, charge to 0.05C at constant voltage, and discharge to 2.0V at 0.33C after standing for 5 minutes. The capacity obtained in this step is the recovery capacity after high temperature storage C3. The recovery capacity retention rate of the battery cell after high temperature storage is calculated to be C3 / C1*100%.

[0151] Among them, Sections 3.3 to 3.5 test the prepared full battery.

[0152] The test results are shown in Table 3.

[0153] Table 3

[0154]

[0155] It can be seen from the above results that Examples 1, 2, and 7 are overall superior in terms of rate performance, high temperature resistance, and cycle performance through the reasonable design of the carbon coating layer and the conductive material, achieving a significant improvement in electrical performance.

[0156] The comparison between Examples 2, 3, 4 and Comparative Examples 1 and 2 shows that as the proportion of organic matter A increases, the proportion of the amorphous carbon layer obtained after carbonization increases, which helps to enhance the liquid retention performance of the electrode, while increasing the active sites for lithium insertion in the negative electrode, thereby improving the overall rate performance of the negative electrode. However, the increase in the amorphous carbon layer will reduce the gram capacity of the negative electrode, resulting in a decrease in energy density. In addition, with the increase in the amorphous carbon layer, the degree of side reactions between graphite and the electrolyte at high temperatures will also increase. This is because the amorphous carbon layer and the conductive material have a large specific surface area and are prone to side reactions with the electrolyte. When the content increases, the degree of side reactions also increases, resulting in deterioration of high temperature performance. Therefore, a reasonable design of the ratio of the amorphous carbon layer to the polymer salt in the carbon coating layer (adjusted by the ratio of organic matter A and the polymer salt) and its content can help achieve a better balance between fast charging and high temperature performance, thereby further optimizing electrical performance.

[0157] The comparison between Examples 2, 5, 6 and Comparative Examples 3 and 4 shows that the conductive material can effectively improve the liquid absorption and retention capacity of the negative electrode sheet, replenish the consumption of the electrolyte during the cycle, shorten the diffusion path of lithium ions in the negative electrode sheet, and reduce the diffusion resistance. The conductive material can also improve the overall electronic conductivity of the negative electrode, thereby improving the fast charging performance and long cycle performance. When the content of the conductive material is too high (>2% of the mass of the negative electrode material), the degree of side reaction with the electrolyte will increase, resulting in a decrease in high temperature performance and initial efficiency, affecting the long cycle performance. In contrast, appropriately reducing the content of the conductive material can more effectively balance these properties and achieve a better overall effect.

[0158] The comparison between Example 2 and Example 8 shows that the second amorphous carbon layer can further improve the liquid absorption and liquid retention performance of the graphite negative electrode, increase the lithium insertion active sites, and thus improve the fast charging performance of the graphite negative electrode. The second amorphous carbon layer can also enhance the bonding strength between the carbon coating layer and the graphite surface, improve the overall structural stability of the negative electrode material, and thus improve the long cycle performance. However, the added amorphous carbon layer may react with the electrolyte and may affect the high temperature performance. Therefore, through the reasonable design of the second amorphous carbon layer, the balance between fast charging performance and high temperature resistance can be better achieved.

[0159] The comparison between Example 2 and Example 9 shows that when the polymer salt and the conductive material surface have matching functional groups, the conductive material tends to be coated on the distribution position of the polymer salt, which is beneficial to improve the electronic conductivity of the negative electrode material, improve the rate performance and cycle performance. The high-temperature storage performance has slightly declined, which may be related to the introduction of functional groups that increase the side reactions with the electrolyte at high temperatures.

[0160] The comparison between Example 2 and Comparative Examples 5 and 6 shows that the polymer salt in the carbon coating layer can effectively improve the desolvation efficiency of lithium ions in the electrolyte on the surface of the graphite negative electrode, thereby significantly improving the fast charging performance. In Comparative Example 5, due to the high carbonization temperature, the second coating layer is completely converted into amorphous carbon, and the consumption of lithium ions during the cycle increases, resulting in deterioration of the cycle performance, and the high temperature performance is also deteriorated due to the increase of amorphous carbon. In addition, carbonization generates inorganic compounds (such as Li2CO3, Na2CO3), which cannot effectively release lithium ions or sodium ions in the electrolyte solvent, lose the effect of ion exchange, and cannot effectively improve the fast charging performance. It can be seen from Comparative Example 6 that when the polymer salt is completely coated on the surface of the amorphous carbon layer, the overall electronic conductivity of the material will deteriorate, which will affect the fast charging performance and cycle performance, but will not affect the high temperature resistance. Therefore, although the presence of the polymer salt significantly improves the fast charging performance, its distribution and structure on the graphite surface need to be reasonably designed. When the polymer salt forms a chimeric structure with the amorphous carbon layer, the overall electrical performance is significantly better.

[0161] In summary, the lithium-ion battery manufactured using the negative electrode material of the present invention not only significantly improves the rate performance, but also improves the stability and tolerance of the battery in high temperature environments. Based on the battery's excellent long cycle performance, fast charging performance and high temperature stability, it can better meet the performance, endurance and service life requirements of new energy vehicles and other electrical devices.

[0162] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A negative electrode material, characterized in that: include: a core, the core comprising a negative electrode active material; a carbon coating layer coating the core, the carbon coating layer comprising a first amorphous carbon layer and a polymer salt embedded in the first amorphous carbon layer; A conductive material is located on the surface and / or inside of the carbon coating layer.

2. The negative electrode material according to claim 1, characterized in that The mass ratio of the first amorphous carbon layer to the polymer salt is 1 to 5:1; and / or the polymer salt is selected from a polymer lithium salt or a polymer sodium salt; and / or the polymer salt contains a carboxyl group with a mass content of 0 to 5%; and / or the mass percentage of the carbon coating layer relative to the negative electrode material is 0.5% to 3%.

3. The negative electrode material according to claim 1, characterized in that The conductive material is selected from at least one of graphene, carbon nanotubes, conductive carbon black, and carbon fiber; and / or the conductive material contains hydroxyl groups, wherein the mass content of hydroxyl groups is 1% to 5%; and / or the mass percentage of the conductive material relative to the negative electrode material is 0.05% to 2%.

4. The negative electrode material according to claim 1, characterized in that The negative electrode active material is selected from at least one of graphite, hard carbon or soft carbon; and / or the particle size Dv50 of the negative electrode active material is 5 to 20 μm.

5. The negative electrode material according to claim 1, characterized in that The surface of the core is coated with a second amorphous carbon layer, and the second amorphous carbon layer is located between the core and the carbon coating layer; optionally, the mass percentage of the second amorphous carbon layer relative to the negative electrode material is 0.5% to 3%.

6. The method for preparing the negative electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, preparing a mixed solution 1 containing an organic substance A and the polymer salt; S2, dispersing the raw materials including the core into the mixed solution 1 to form a mixed solution 2; S3, drying the mixed solution 2, and then sintering it under a protective atmosphere to carbonize the organic matter A therein to form a carbon coating layer covering the core; S4, preparing a mixed solution 3 containing a conductive material, dispersing the product obtained in step S3 in the mixed solution 3, and obtaining the negative electrode material after drying; Or include the following steps: S1', preparing a mixed solution 4 containing the polymer salt, organic matter A, core and conductive material, drying the mixed solution 4, and then sintering it under a protective atmosphere to carbonize the organic matter A to obtain the negative electrode material.

7. The preparation method according to claim 6, characterized in that: A dispersant is further added to the mixed solution 3, and step S4 further includes: carbonizing the dispersant after drying to obtain the negative electrode material; or, a dispersant is further added to the mixed solution 4, and in step S1', the organic matter A and the dispersant are carbonized by sintering to obtain the negative electrode material; Optionally, the solid-liquid mass ratio of the mixed solution 2-4 is independently selected from 1:1 to 5; Optionally, when the negative electrode material further includes a second amorphous carbon layer, the method for preparing the negative electrode material further includes: before step S1, coating the surface of the core with the second amorphous carbon layer; Optionally, the organic matter A is selected from one or more of ethylene tar, coal tar, coal pitch, rubber plasticizer, styrene-butadiene rubber, urea-formaldehyde resin, monosaccharide compound, polysaccharide compound, carboxymethyl cellulose or its salt, polyacrylate or polyacrylate; Optionally, the dispersant is selected from at least one of polyvinylidene fluoride or its derivatives, carboxymethyl cellulose or its derivatives, salts of carboxymethyl cellulose or its derivatives, polyvinyl pyrrolidone or its derivatives, polyacrylic acid or its derivatives, polyacrylic acid salts, polystyrene-butadiene rubber, polyacrylamide, polyimide, polyamide-imide, and phenolic resin; Optionally, the mass ratio of the dispersant to the conductive material is 1:1 to 10; Optionally, the carbonization temperature of the organic matter A is T1, the carbonization temperature of the polymer salt is T2, the softening temperature of the polymer salt is T0, the sintering temperature is T, and T, T0, T1, and T2 satisfy the following relationship: T1<T<T2, and T0<T.

8. A negative electrode sheet, characterized in that: The raw material for preparing the negative electrode sheet includes the negative electrode material as described in any one of claims 1-5.

9. A secondary battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 8; optionally, the secondary battery is a lithium ion battery or a sodium ion battery.

10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.

Citation Information

Cited By

  • Negative electrode material, preparation method therefor, and use thereof

    WO2026097859A1